Situs Perahu Kuno dan Perahu Besi di Bojonegoro - Intan, Marshanda Fitria (Lambung Mangkurat University, 2022)
The issuance of the Canggu inscription illustrates that Bojonegoro was one of the areas through which the Bengawan Solo flow passed, which played an important role in trading activities. So don't be surprised if you find many relics such as coins, pottery, boats and others. The boats that have been found at the bottom of the Bengawan Solo river in Bojonegoro are an ancient boat in Padang Village, Trucuk District which was found in 2005 and an iron boat in Ngraho Village, Gayam District which was lifted to the mainland in 2013. briefly about the existence of Bengawan Solo and the crossing villages as well as explaining the ancient Trucuk boat and the Ngraho iron boat from the initial discovery conditions to the present day. It is hoped that readers will be able to know the historical evidence of the glory of Bengawan Solo, namely by knowing and understanding the findings of ancient boats in Bojonegoro which have historical value. The method used in this study is a historical research method which is divided into heuristics, verification, interpretation and historiography.